Encontros e desencontros do Movimento Estudantil Secundarista Paranaense (1964 1985). - Schmitt, Silvana Lazzarotto (2011)
This study aims to explain the characteristics of the high school students organization in the period from 1964 to 1985. The time frame is justified insofar as it represents the exercise of a military government in which students and other sectors of society were organized to break with many actions of this government. The study focused on the high school student movement in the state of Paraná (Brazil), since there is no literature produced on this form of student organization, and since we believe that it contributed in the way the military government was organized. During data collection, we found great difficulty in consulting the sources, since the ones dealing specifically with the object of study were primary sources and, as it is already known to many, history has been showing that there is no interest in filing some kinds of documents, especially from a period in the history of the country with so many obscure events. The study on the high school student movement in Paraná was carried out in light of the social, economic and political aspects of the reporting period. The primary sources were analyzed on the basis of a theoretical framework which would propitiate systematic and accurate use of data. The secondary sources dealt with the way society was organized in that period and the production concerning the Brazilian student movement, either the university or the high school one. In order to elucidate how high school students from Paraná were organized during that period, this dissertation is organized into four chapters. The first two chapters aims to provide context for the reader, bringing to the debate, firstly, the strongest period of civil-military dictatorship (1964-1974), and secondly, the process of political opening. In both chapters the government s and student movement s actions are highlighted. In the following chapter, we examine the primary sources, which consist of documents filed in the Public Archives of Paraná that are part of DOPS-PR Archives. The last chapter focuses on the study of memory through a brief analysis of the interviews conducted with some activists of the high school movement in Paraná, and through the discussion on the contrasts between the story "told" by the activists and what is written in official documents of the period.